Role of preoptic opioid receptors in the body temperature reduction during hypoxia - Scarpellini, Carolina da Silveira [UNESP]; Gargaglioni, Luciane H. [UNESP]; Branco, Luis G. S.; Bicego, Kenia C. [UNESP] (Elsevier B.V., 2009)
Evidence indicates that endogenous opioids play a role in body temperature (Tb) regulation in mammals but no data exist about the involvement of the specific opioid receptors, mu, kappa and delta, in the reduction of Tb induced by hypoxia. Thus, we investigated the participation of these opioid receptors in the anteroventral preoptic region (AVPO) in hypoxic decrease of Th. To this end, Th of unanesthetized Wistar rats was monitored by temperature data loggers before and after intra-AVPO microinjection of the selective kappa-opioid receptor antagonist nor-binaltorphimine dihydrochloride (nor-BNI; 0.1 and 1.0 mu g/100 nL/animal), the selective mu-opioid receptor antagonist D-Phe-Cys-Tyr-D-Trp-Arg-Thr-Pen-Thr-NH(2) cyclic (CTAP; 0.1 and 1.0 mu g/100 nL/animal), and the selective delta-opioid receptor antagonist Naltrindole (0.06 and 0.6 mu g/100 nL/animal) or saline (vehicle, 100 nu animal), during normoxia and hypoxia (7% inspired O(2)). Under normoxia, no effect of opioid antagonists on Th was observed. Hypoxia induced Th to reduce in vehicle group, a response that was inhibited by the microinjection intra-AVPO of nor-BNI. In contrast, CTAP and Naltrindole did not change Th during hypoxia but caused a longer latency for the return of Th to the normoxic values just after low O(2) exposure. Our results indicate the kappa-opioid receptor in the AVPO is important for the reduction of Th during hypoxia while the mu and delta receptors are involved in the increase of Th during normoxia post-hypoxia. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Thermoregulation; Delta; Kappa; Mu; Naltrindole; CTAP; Nor-BNI